Religion, Economics and Social Thought: By Walter Block and Irving Hexham (eds.). Vancouver, BC: The Fraser Institute, 1986. (American Journal of Islam and Society, 1991)
This is a wide-ranging and fascinating collection of papers dealing withthe impact of religion on what may be called the social economy. It is anecumenical volume in that it begins with the Catholic Church then considersseveraJ forms of Protestantism, then goes on to discus Judaism, and finallyconsiders Islam. It should be clear that the volume is predominantly "Christian,"but the effort to include the other monotheistic religions is very welcome.One difficulty in reviewing this volume is that many of the papers areinformative but not representative of the religious traditions they represent.Thus A. M. C. Waterman's piece describes a particular phase of Anglicansocial thought, and the same is true of the one by Paul Heyne. Perhaps anoverview is po ible only for those movements which are no longer active,a in Ronald Preston's fine contribution on Christian Socialism in Britain.I must confess some surprise on finding the vigor with which any perceiveddefect of the market was defended.For Muslims, some of the most interesting points about this volume areto be found in the instances of active politicians who took strong religiousstands. Abraham Kuyper's vision of neo-Calvinism is the outstanding examplein the paper by Bob Goudzwaard, but Waterman's presentation of PrimeMinister Margaret Thatcher's views are equally revealing. Of less practicalimport, but nonetheles equally intriguing, is the account by John Yoder ofthe "First Reformation" in Czechoslovakia as well as the reasons for the neglectof this movement-lack of political support, linguistic distance from We ternEurope, and an ab ence of shared doctrinal formulations.The description of Judaism and the Market Mechanism by Meir Tamariprovides many parallels with Islamic market supervi ion, and there is even ...